A Moral Reading of Argentine Constituional Case Law (Prudentia Iuris, 2018)
Resumen: Como han remarcado varias escuelas de filosofía del derecho, la naturaleza abstracta del lenguaje constitucional, significa dejar una puerta abierta para diversas apreciaciones políticas, éticas y filosóficas. En dicha línea, Ronald Dworkin ha sostenido insistentemente que la dimensión creativa, moral y teleológica de la interpretación legal no es excepcional ni separable de una comprensión neutral de las fuentes legales de manera independiente. Abstract: As has been previously remarked by various legal-philosophical schools of thought, the abstract nature of constitutional language remains an open door to political, ethical, and philosophical assessments. As Ronald Dworkin has insistently sustained that the creative, moral, and teleological dimension of legal interpretation is neither exceptional, nor separable from a neutral understanding of legal sources independently